EFFECT OF TOURISM ON THE LABOUR MARKET IN LUANGPRABANG, LAO PDR - JOHN WALSH (ASEAN Journal on Hospitality and Tourism, 2010)
People in the tourism industry in Luang Prabang have garnered some background, knowledge and experience of the industry. However, they need to improve their abilities in order to keep afloat in a competitive business environment. Developing the labour market in Luang Prabang is difficult, though, because of the lack of an overall development plan, the scarcity of individual motivation, limited budgets, the shortage of qualified people in the tourism management field in either the private or public sectors and limited collaboration for tourism development. Research findings are reported upon concerning these issues and recommendations are provided for rectifying the shortcomings identified and strengthening the sustainable development of the tourism industry of Luang Prabang.